PENGARUH RASIO LIKUIDITAS, PROFITABILITAS, LEVERAGE, DAN EPS TERHADAP RETURN SAHAM (Students' Journal of Accounting and Banking, 2012)
This study aims to examine the effect of financial ratios that proxy for liquidity in his CR, proks fish profitability in ROA, leverage is in the proxy's DER and Earning Per Share (EPS) of the stock returns of manufacturing firms listed on the Stock Exchange in 2008 - of 2010. Document for the study was taken from the manufacturing company's financial statements that are still active on the Stock Exchange in the year 2008-2010, has a complete data during the observation period financial statements, using the rupiah exchange rate in the financial statements are examined. Sampling method using a purposive sampling method produces 121 companies. The results of the study showed positive and significant effect of EPS on stock returns, while CR and ROA is positive and significant effect on stock returns, and the DER and the significant negative effect on stock returns. For further research is recommended to add the variable size of the company.Keywords : Stock Return, Profitability, Liquidity, Leverage, Earning Per Share